Cognitive function and speech outcomes after cochlear implantation in older adults - Tadao Yoshida; Masumi Kobayashi; Daisuke Hara; Rikako Taniguchi; Yukari Fukunaga; Michihiko Sone (Frontiers in Neurology, 2025)
BackgroundThe impact of cochlear implantation on cognitive function in older adults and the relationship between preoperative cognitive ability and postoperative speech perception remain poorly understood. In this study, we aimed to evaluate the effect of cochlear implant use on cognitive function in older adults and to explore the association between preoperative cognitive ability and postoperative speech discrimination.MethodsWe conducted a retrospective cohort study at a university hospital between June 2017 and March 2025. Thirty cochlear implant recipients aged ≥61 years were included, with 21 receiving unilateral implants and nine receiving bilateral implants. All participants underwent cognitive assessments both preoperatively and postoperatively. We analyzed the cognitive function test results before and after cochlear implantation. The primary outcomes measured were: (1) the correlation between preoperative cognitive test scores and postoperative speech discrimination scores; and (2) longitudinal changes in postoperative cognitive function.ResultsA significant positive correlation was observed between preoperative Kohs Block Design Test scores and postoperative speech discrimination scores (p < 0.01). Preoperative Raven’s Colored Progressive Matrices scores also correlated positively with postoperative speech discrimination scores (p < 0.05). Postoperatively, Kohs scores demonstrated significant positive correlations with both the Mini-Mental State Examination (p < 0.01) and Reading Cognitive Test Kyoto test (p < 0.0001) scores. Following a 3.7-year mean follow-up, Kohs scores remained stable, with some patients showing improvements.ConclusionCognitive assessments performed during the preoperative CI evaluation may yield valuable insights into postoperative outcomes in older adults. Additionally, long-term postoperative cognitive function is generally preserved, with the potential for improvement following cochlear implantation.